Gender in Emergency Services: Foundations for Greater Equity in Professional Codes of Ethics. (2nd November 2021) - Bishu, Sebawit; McCandless, Sean; Elias, Nicole
Abstract : The lack of gender equity in the public sector is a critical issue, especially for emergency services. We explore the gendered nature of firefighting and policing at both professional and organizational levels. We assess gender equity by asking the following questions: (1) How have understandings of gender in emergency services evolved over time? (2) What are the normative implications of emergency services' lack of gender equity? We draw from feminist literature to critique the lack of progress and examine firefighting and policing histories along with the professional ethics codes of the U.S. Fire Administration and the International Association of Chiefs of Police. This analysis demonstrates the potential to foster greater gender equity in emergency services and other public organizations by suggesting means of improving ethics codes that serve as foundations for organizational cultures, policies, and practices